Damages and failures of plastic pipes and liners in trenchless rehabilitation of sewers - Kuliczkowski, Andrzej; Kuliczkowska, Emilia (Instal, 2023)
A list of possible damages to pipes and liners used in trenchless rehabilitation of sewers using the CIPP method was made, based on British, American, New Zealand and European methods. There are descriptions of 7 failures of pipes and rehabilitation liners that occurred within 3 years after the completion of works. An analysis of the causes of the occurrence these failures was made.